Earthquakes and crush syndrome casualties: Lessons learned from the Kashmir disaster - KOÇ, MEHMET (ELSEVIER SCIENCE INC, 2007)
Major earthquakes may provoke a substantial number of crush casualties complicated by acute kidney injury (AKI). After the 1988 Armenian earthquake, the International Society of Nephrology (ISN) established the Renal Disaster Relief Task Force (RDRTF) to organize renal care in large disasters

this approach proved to be useful in several recent disasters. This paper depicts the organizational aspects of the rescue intervention during the Kashmir earthquake, in 2005. Specific problems were fierce geographic circumstances, lack of pre-registered local keymen, transportation problems, and inexperience of local teams to cope with problems related to mass disasters. Once treatment was installed, global outcomes were favorable. It is concluded that well-organized international help in renal disasters can be effective in saving many lives, but still necessitates conceptual adaptations owing to specific local circumstances.
Keywords: Pakistan; Kashmir; earth quake; crush syndrome; rhabdomyolysis; ACUTE-RENAL-FAILURE; MARMARA EARTHQUAKE; VICTIMS; MORTALITY; DIALYSIS; INJURIES; MANAGEMENT; MORBIDITY; RESCUE; IRAN